Strategy Analysis of Product Selling Prices and Product Quality on Purchase Decisions and Its Impact on Wuling Confero LMPV’s Customer Loyalty in Jabodetabek - Prabowo, Aldo Yuli; Salim, Agus (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This research has purpose to deep dive the impact caused by product selling price strategy as well as product quality on purchase decisions and its effectiveness towards consumer loyalty. The population used in this study were all Wuling Confero LMPV users in Jabodetabek with total sample of 190 respondents. Quantitative methods has been used as the research design. The techniques which applied for collecting data is by the use of survey methods through questionnaires. And it proceed with assists of PLS-SEM analysis method. Its results show that: 1) Selling price and product quality have significantly positive impact on purchase decisions and consumer loyalty 2) purchase decisions have significantly positive effect on consumer loyalty 3) purchase decisions play an important role in mediating the effectiveness of Selling price and product quality on consumer loyalty.